Advancing trial design in progressive multiple sclerosis. (October 2017) - Fox, Robert J; Chataway, Jeremy
The failure of a majority of clinical trials in progressive multiple sclerosis (MS) has highlighted the need to reconsider how these trials are designed and conducted, and many areas deserve focus. Basic scientists are reconceptualising the pathophysiology of progressive MS into three broad areas: systemic inflammation, compartmentalized inflammation and non-inflammatory neurodegeneration, with the latter two becoming predominant as the disease progresses. This framework will guide the choice of experimental therapies. Previous clinical trials have highlighted how participant selection can have a significant impact on study outcome. Phase 2 biomarkers which are biologically stable, dynamically changing over time, and easy to assess in multi-centre studies are greatly needed. Shortcomings inherent in the Expanded Disability Status Scale are prompting the development and validation of better clinical measures. The standard two-arm, fixed-duration trial paradigm has been challenged with new, innovative approaches that can test more therapies efficiently. International collaboratives such as the Progressive MS Alliance will support increased dialogue with regulators, industry and other funding agencies. Better engagement with people living with progressive MS will transform them from simply being the recipient of MS therapies to partners in the search for new treatments. Focused, targeted action will drive further development of effective therapies for progressive MS.